The Influence Of Work Motivation And Leadership On The Performance Of Village Apparatus In Semumu Village, Depati VII - Edwin Bustami; M Dhany al sunah; Afrianti; Nurfitri (PT Maju Malaqbi Makkarana, 2026)
The purpose of this research is to determine The Effect Of Work Motivation And Leadership On The Performance Of Village Officials In Semumu Village, Depati VII District. The data analysis method uses multiple linear regression analysis. The data collection technique used was a questionnaire. The population of this study consisted of all village officials and community members, totaling 30 individuals, and used a saturated sampling method. The type of research used in this study is a quantitative approach, with multiple linear regression testing, conducting validity and reliability tests on the statement items of each variable, as well as T-tests and F-tests, processed using SPSS version 23. The research results show that the independent variable of work motivation has no significant effect on employee performance when considered individually, while leadership has a significant effect on employee performance. The results of simultaneous regression analysis from the ANOVA test or F test yielded an F value of 4.186 with a significance level of 0.026. Because the significant probability is much smaller than 0.05, this indicates that it can be concluded that there is a simultaneous effect of work motivation and leadership on employee performance.